Pathology of the Pleura and Mediastinum (Encyclopedia of Pathology,, 2018)
This book covers the complete field of pleura and mediastinum pathology - from acquired multilocular thymic cyst to well-differentiated papillary mesothelioma. The alphabetically arranged entries, each of which provides a detailed description of a specific pathological disease pattern, allow readers to quickly and easily find the information they need.